Origin of human blastocysts aneuploidies analyzed by single nucleotide polymorphism microarra y with Parental Support - Gazzo Benavides, Eduardo (2014)
Background: Preimplantation genetic screening (PGS) using comparative genomics hybridization  (aCGH) and single nucleotide polymorphism (SNP) technology has become a useful tool in assisted reproduction by improving clinical outcomes. Both techniques identify aneuploidies and chromosomal rearrangement. However, SNPs with Parental Support (Natera Inc.) give extra information of the aneuploidy origin either from the sperm or the oocyte. Objectives: To determine single aneuplodies rate in human embryos obtained by assisted reproduction using single nucleotide polymorphism microarray. Design: Retrospective study. Setting: Grupo PRANOR, Sede Monterrico, and Genomics Peru, Lima, Peru. Biologic material: Human embryos. Interventions: From 2011 to 2013, 105 patients underwent IVF/ICSI with SNPs and Parental Support. In total, 429 embryos were analyzed and records were reviewed. Main outcome measures: Embryos aneuploidy, relation with maternal age and paternal or maternal origin. Results: From the 429 embryos 208 (48.8%) were chromosomally normal. The proportion of normal embryos decreased with increasing maternal age. In all age groups more than 66% of aneuploidies had maternal origin, including the ovodonation group (OD). Conclusions: PGS by SNPs with Parental Support resulted in good prognostic value and would be useful in determining the origin of aneuploidy in embryos of patients who underwent assisted reproduction technology.